U.S. Foreign Policy Towards Taiwan: Obama vs. Trump - Nur Seda TEMUR (Alınteri sosyal bilimler dergisi, 2020)
As Donald Trump won the vote in the U.S. presidential elections in 2016, many anticipated a number of changes in the U.S. foreign policy. In this sense, China and Taiwan were not exceptions. With respect to this outcome, this paper will address the following question: How did the U.S. Foreign Policy towards Taiwan change from the Obama administration to the Trump administration? Regarding this question, in this paper, I will try to defend the view that as long as U.S.- China economic rivalry and trade war persists, Taiwan will remain under U.S. protection, regardless of a change in administrations in the U.S. This study will be a qualitative case study. In particular, in order to compare the U.S. foreign policy towards Taiwan under Obama and Trump administration, the data will be gathered from secondary resources through document analysis. These sources will be composed of relevant books, articles, academic journals, research papers, and newspapers gathered from libraries. These sources will be used for elaborating on foreign policies of Obama and Trump administration on Taiwan.